UPAYA MEMPERJUANGKAN PERATURAN DAERAH TENTANG PENGAKUAN, PERLINDUNGAN DAN PEMBERDAYAAN MASYARAKAT HUKUM ADAT KASEPUHAN KABUPATEN LEBAK, BANTEN - Desmiwati Desmiwati; Surati Surati (Jurnal Analisis Kebijakan Kehutanan, 2018)
The Constitutional Court (CC) Decree Number 35/PUU- /2012 had determined that customary forests are no longer classified as state forests. However, the isssue of restoring customary forests in to their right holders is still challenging. This study aims to analyze the text of the regional regulation of Lebak Regency Number. 8 of 2015, the process of passing the regional regulation and sociocultural practiced of this regulation. The research was conducted in customary law community of Kasepuhan, Lebak Regency, Banten Province. Data analysis was carried out using Norman Fairclough’s critical-discourse model and descriptive analysis by data retrieval through documentation, interview and literature study. The result found that Regional Law on the Recognition, Protection and Empowerment of Kasepuhan Customary Law Community has accommodated the needs of this indigenous community to defend their territories. Nevertheless, in its implementaion there is still problem related to the central government, the Ministry of Environment and Forestry, as some of the customary areas are overlapping with the area of Gunung Halimun Salak National Park. Hence, the potential conflict still occurs. Conflict resolution can be anticipated through synergetic collaborative management among related stakeholders to realise  forest sustainability.